Peningkatan Motivasi Dan Hasil Belajar Tema 1 Muatan IPA Perkembangbiakan Tumbuhan Dan Hewan Menggunakan Model Blended Learning Berbantuan Video Melalui Group Whatsapp Pada Peserta Didik Kelas VI SDN Pepedan Tahun Pelajaran 2020/2021 (Wiyatamandala, 2021)
ABSTRACTThe study was conducted to determine the increase in motivation and learning outcomes of grade VI students at SDN Pepedan for the academic year 2020/2021 through the application of a blended learning model assisted by video media through whatsapp groups in thematic learning of science content on the subject matter of plant and animal reproduction. This research is Classroom Action Research (CAR) for 2 cycles. The instruments are observation sheets, questionnaires and questions. The data analysis technique is descriptive quantitative. The results show that the application of the Blended Learning Learning Model increases motivation and learning outcomes. The increase is seen from the percentage score of observations and questionnaires. Learning Motivation is 64.32% to 68.49% in the first cycle, in the second cycle it increases from 68.49% to 79.69%. Meanwhile, learning outcomes increased from 7 students (43.75%) to 11 students (68.75%) who finished studying. In the second cycle, it increased again to 16 students (100%) who met the KKM, which was 65.Keywords: Blended Learning Model; Motivation to learn; Learning outcomes. ABSTRAKPenelitian dilakukan untuk mengetahui peningkatan motivasi dan hasil belajar peserta didik kelas VI SDN Pepedan tahun pelajaran 2020/2021 melalui penerapan model pembelajaran blended learning berbantu media video melalui group whatsapp pada pembelajaran tematik muatan IPA materi pokok perkembangbiakan tumbuhan dan hewan. Penelitian ini adalah Penelitian Tindakan Kelas (PTK) selama 2 siklus. Instrumennya lembar observasi, angket dan soal. Teknik analisis datanya deskriptif kuantitatif. Hasilnya menunjukkan Penerapan Model Pembelajaran Blended Learning meningkatkan motivasi dan hasil belajar. Peningkatan dilihat dari skor persentase observasi dan angket. Motivasi Belajar 64,32% menjadi 68,49% di siklus I, di siklus II meningkat dari 68,49% menjadi 79,69%. Sedangkan hasil belajar meningkat dari 7 peserta didik (43,75%) meningkat 11 peserta didik (68,75%) yang tuntas belajar. Pada siklus II meningkat lagi menjadi 16 peserta didik (100%) yang memenuhi KKM yakni sebesar 65.Kata Kunci: Model Pembelajaran Blended Learning; Motivasi Belajar; Hasil Belajar.